The economics of home grown forestry - Putz, F.E. (2000)
Costs of applying silvicultural treatments prescribed to increase yields of timber and non-timber forest products from natural forests should be calculated differently for industrial logging companies, private non-industrial forest owners, and community based forest management operations. For forest owners who are not concerned solely with maximising short-term profits from their forests, the opportunity costs of forest labour are often lower than official minimum wages. Furthermore, for forest owners who do not have ready access to interest accruing savings mechanisms or where bank solvency is in question, the opportunity costs of waiting for long rotation forest crops to mature may not be as high as public interest rates would suggest. Both the true costs of management and the multitude of marketed and non-marketed benefits from well-managed natural forests need to be considered when assessing forestry as one component of a diverse portfolio of conservation options.